Race- associated molecular differences in uterine serous carcinoma - Lara, Olivia D.; Karpel, Hannah; Friedman, Steven; Hacker, Kari E.; Pothuri, Bhavana (Frontiers in Oncology, 2024)
PurposeEndometrial cancer (EMCA) is the most common gynecologic malignancy, and new diagnoses are increasing in the United States. Black patients are more likely to present with advanced stage, be diagnosed with high-risk uterine serous carcinoma (USC) and die of their cancer.MethodsPatients with endometrial adenocarcinoma who received tumor FoundationOne CDx testing at our institution between January 2017 and August 2022 were identified. Genomic alterations, demographic and clinical characteristics were collected. Descriptive statistics and Fisher’s exact test were used to analyze data.ResultsA total of 289 patients (29.4% Black and 52.6% White) with advanced or recurrent endometrial adenocarcinoma underwent FoundationOne CDx testing. USC comprised 26.3% (76 of 289) of tested tumors. Of USC tumors, 33 of 76 (44%) were of Black race. USC occurred more frequently in Black patients (33 of 85 [38.8%] Black patients compared to 30 of 152 [19.7%] White patients, p<0.05). Among USC, CCNE1 amplification occurred more frequently in Black patients than in White patients (12 of 33 [36.36%] vs 2 of 30 [6.67%], p<0.05) while PI3K/AKT/mTOR pathway mutations occurred less frequently (16 of 33 [48.5%] vs 26 of 33 [86.7%], p=0.17). Among patients with CCNE1 amplification 73.3% (11 of 15) progressed on or within 12 months of first-line platinum-based therapy. CCNE1 amplification had significantly shorter median overall survival (97.3 months vs 44.3; HR (95%CI): 7.1 (10.03, 59.4) p< 0.05).ConclusionsBlack patients constituted 44% of patients with USC in our study and had an increased frequency of CCNE1 amplification. Patients whose tumors harbored CCNE1 amplification had shorter overall survival. Identifying actionable mutations in this high unmet need population is crucial to improving outcomes among Black patients with uterine malignancy. Development of new targeted-therapies will need to keep these alterations at the forefront as trials are being designed.